Luminescence properties of AgTb(WO4)2 doped with Ce3+: Experimental determination of the Stern-Volmer quenching constant. Issue 8 (1st June 2017) - You, Chaoyu; de Andrés-García, Isabel; Fernández-Martínez, Francisco; Colón, Cristóbal
Abstract: Scheelite-like AgTb(WO4 )2 doped Ce 3+ were synthesized by ceramic method. Efficient characteristic bands of Tb 3+ were observed in AgTb(WO4 )2 compounds. However, the presence of Ce 3+ quenched the emission band of Tb 3+ which can be caused by metal-to-metal charge transfer between Tb 3+ /Ce 3+ . The quenching is more efficient at high temperature which can be attributed to more overlaps of wave functions of Ce 3+ -W 6+ -Tb 3+ at high temperature. The experimental Stern-Volmer quenching rate constant at room temperature and liquid nitrogen temperature were measured as (376±4)·10 −3  μs −1 (x content/mol) −1 and (45±4)·10 −3  μs −1 (x content/mol) −1 respectively. In excitation spectra, evident blue shift of charge transfer band in the case of liquid nitrogen temperature was observed. In addition, the blue shift of CT band also occurred with increasing concentration of Ce 3+ . The shifting of charge transfer band can be interesting to the design of solar cells and tunable excitation sources and detectors.